Approaches for reducing wastes in the agricultural sector. An analysis of Millennials' willingness to buy food with upcycled ingredients. (1st May 2021) - Coderoni, Silvia; Perito, Maria Angela
Highlights: The bulk of Millennial consumers surveyed knows food with upcycled ingredients. Millennials show positive purchase intentions for food with upcycled ingredients. Food Neophobia and Food Technology Neophobia negatively impact willingness to buy. Purchase intentions are shown for food that benefit health and environment. Abstract: Upcycled ingredients are one of the most significant current trends in the food industry aimed to tackle the challenge of solid food loss reduction. This study investigates the potential market among Millennial consumers for products enriched with upcycled ingredients in Italy. We surveyed a sample of 317 Italian Millennial consumers, using a web-based survey. 62% of respondents declared to be informed about the existence of food made from upcycled ingredients and 53% declared to be willing to buy this novel food. Also, 69% of respondents think that food enriched with upcycled ingredients can bring environmental benefits, while only 40% believe that it can bring health benefits. Using a logit model to analyse consumer preferences, we found that food neophobia and food technology neophobia negatively impact on the likelihood of being willing to buy food produced with upcycled ingredients. Also, consumers who give high importance to food certification are less likely to be willing to buy upcycled foods. Contrariwise, reading labels and believing that upcycled foods are healthier or more environmentally friendly positively impacts on the willingness of Millennial consumers to buy these foods. Results for the sample analysed eventually suggest that giving right information to consumers about the environmental and health characteristics of the products, through clear labelling, could increase their market uptake thus helping to reduce food loss and contributing to reaching circular economy objectives in the agricultural sector.